Kallmann syndrome: MR evaluation of olfactory system. - Yousem, D M; Turner, W J; Li, C; Snyder, P J; Doty, R L (American Journal of Neuroradiology, 1993)
PURPOSE To describe the MR appearance of the olfactory bulbs and tracts and temporal lobes in patients with Kallmann syndrome, a disorder characterized by hypogonadotropic hypogonadism and anosmia.METHODS High-resolution MR scans with a surface coil placed over the nasion were performed in two patients with Kallmann syndrome. Coronal 3-mm thick contiguous sections were obtained through the olfactory bulbs and tracts. MR scans included volumetric analysis of the bulbs, tracts, temporal lobes, and hippocampi.RESULTS No olfactory bulbs or tracts could be identified in patients with Kallmann syndrome. In comparison, the olfactory bulbs and tracts were identifiable in seven healthy volunteers. The temporal lobe and hippocampal volumes were comparable between control subjects and Kallmann patients.CONCLUSIONS High-resolution surface-coil MR can identify the absence of olfactory bulbs and tracts in patients with Kallmann syndrome. Normal olfactory bulbs and tracts are easily discerned with surface-coil imaging.